1977
DOI: 10.1530/acta.0.0860001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Luteinizing Hormone-Releasing Hormone in Hypogonadotrophic Eunuchoidism

Abstract: Fourteen patients with hypogonadotrophic eunuchoidism (HE), 10 males and 4 females, received luteinizing hormone-releasing hormone (LH-RH) as 4-h intravenous infusions of 0.2 \g=m\g/min or as subcutaneous (sc) injections of 200 \g=m\g.Repeated LH-RH administration over 4 days (200 \g=m\g sc daily) was undertaken in 8 patients. Eight of the 10 males and all 4 of the females were found to have definite elevations of luteinizing hormone (LH) and follicle stimulating hormone (FSH) following their first exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…It is also documented that basal and LRH-stimulated LH secretion is more dependent on previous LRH stimulation than is FSH secretion (Bremner et al -1977;Jacobson et al -1979). The differences, shown in our experiments, between the LH and FSH response to LRH after administration of tamoxifen, support the concept of different sites of negative feedback action of estrogens on LH and FSH secretion.…”
Section: Discussionsupporting
confidence: 82%
“…It is also documented that basal and LRH-stimulated LH secretion is more dependent on previous LRH stimulation than is FSH secretion (Bremner et al -1977;Jacobson et al -1979). The differences, shown in our experiments, between the LH and FSH response to LRH after administration of tamoxifen, support the concept of different sites of negative feedback action of estrogens on LH and FSH secretion.…”
Section: Discussionsupporting
confidence: 82%
“…Serum levels of FSH were undetectable in a radioimmunoassay that is sufficiently sensitive to differentiate reliably between the low end of the normal adult range and the values found in prepubertal boys or hypogonadotropic subjects (28). Serum levels of FSH in this assay were always undetectable in basal sampling in the men during hCG plus T administration in this study, even when sampling was at 20-min intervals for 6 h. Infusion of LHRH demonstrated that even with 4 h of stimulation, four of five subjects failed to increase their FSH levels into the detectable range, whereas the fifth man had a slight increase late in the infusion.…”
Section: Resultsmentioning
confidence: 94%
“…A possible explanation of these data is that there may be a relatively high production of endogenous LHRH in neonatal animals, which leads to an increase in the acutely releasable pool of LH (15,16). These responses in the youngest animals were greater than those in older prepubertal animals, and for LH, were as great as those found in adults.…”
Section: Discussionmentioning
confidence: 93%